Experimental study on the nozzle-shape effect on liquid jet characteristics in gaseous crossflow - Jalili, B.; Jalili, P.; Ommi, F.; Ganji, D. D. (Frontiers in Mechanical Engineering, 2023)
This study presents experimental findings on the crossflow injection of a liquid jet into a gaseous flow. Crossflow injection is favored over co-axial trajectory injection because of its potential to enhance atomization, promote the formation of smaller droplets, and improve injection parameters, mainly due to the differing trajectory of fuel injection within the transverse airflow. The study’s experiments use two circular and four elliptical nozzles with varying aspect ratios. The research investigates the influential factors that affect the trajectory and breakup of the liquid jet, specifically analyzing the impact of the nozzle geometry, Weber number, and momentum ratio of the liquid jet to the air crossflow. Additionally, equations are derived to describe the trajectory for both elliptical and circular nozzles. The relationship between breakup height and length is explored, with the observation that breakup length remains constant for both nozzle shapes. Furthermore, the study investigates the analysis of breakup regimes and establishes a direct correlation between the Weber number and the breakup regime. Column, bag, and multimode breakup are observed at Weber numbers 4, 38, and 82, respectively. The experimental error for the liquid jet trajectory obtained is approximately 2%. Importantly, the experimental results align with previously published experimental and numerical data, confirming the validity and reliability of the findings.